Effect of Nucleotides Supplementation on Growth Performance, Humoral Immunity, and Intestinal Morphological Structure of Broiler Chickens - Trairatapiwan, Tassanee; Lertpatarakomol, Rachakris; Jaipeng, Patiparn; Paditporn, Kornkamon (Journal of Mahanakorn Veterinary Medicine, 2017)
Feeding nucleotides in young animals is believed to have benefit effects such as improving growth rate, enhancing gut health and immune system. Thus, the aim of this present study was to evaluate the effect of nucleotides supplementation in diets at difference periods on growth performance of broiler chickens. A total of 180 Ross 308 (mixed sex), one-day-old broiler chickens were randomly distributed in completely randomized experimental design (CRD) into 3 treatments with 4 replicates of 15 birds in each. The experimental treatments consisted of: birds fed control diet, birds fed 1.5% nucleotides for the first 7 days of age and birds fed 1.5% nucleotides for the first 14 days of age. The dietary period was divided in two phases: starter diet (1 to 21 days) and grower diet (21 to 42 days). The result showed that, at 42 days of ages, there were no significantly difference (P>0.05) in body weight gain, feed intake, feed conversion ratio and HA-HI titer of broiler serum antibodies specific to ND virus between treatments. However, broilers fed with nucleotides had a significant higher (P<0.05) villus height than those fed with control diet. In conclusion, the current study demonstrated that feeding broiler chickens with 1.5%nucleotides in the diet tended to improve growth performance and intestinal morphology of broiler chickens.